A series of unfortunate events - Snicket, Lemony (Sl : Dream Works Home Entertainment, 2005)
When their wealthy parents are killed in a fire, the three Summary: Baudelaire orphans, Klaus, Violet and Sunny, are sent to live with a distant relative, the evil Count Olaf. They soon find out that he is plotting to kill them and seize their fortune.
Cast: Carrey, Jim, 1962-
Keywords: Film adaptations; Film